The Effect of Mergers and Acquisitions on the Financial Performance of Companies Listed on the Indonesia Stock Exchange - Fadila, Ega; Kusumaningtyas, Meisya; Hidayati, Arrina; Panggiarti, Endang (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Mergers and acquisitions are strategic maneuvers involving the consolidation of two or more companies, aiming to improve overall company performance and gain a competitive advantage. This research seeks to evaluate the impact of mergers and acquisitions on the financial performance of companies listed on the Indonesia Stock Exchange. Using the PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses) methodology, this research employs a literature review approach. Secondary data from various sources, including books, e-books, journals, and current news, were examined. The results suggest that mergers and acquisitions do not significantly impact the financial performance of companies. This may be due to the fact that the purpose of mergers and acquisitions is more focused on long-term aspects. The theoretical underpinning of this research centers on the understanding that mergers and acquisitions, as strategic actions, may not significantly influence the financial performance of companies in the short term. The results of the literature review indicate that there is no substantial impact on financial performance. This finding suggests that the primary objectives of mergers and acquisitions may be more aligned with long-term considerations, such as market positioning, synergies, and strategic growth, rather than immediate financial gains.